A imposição do inglês como política linguística : na contramão do plurilinguismo - Fonseca, Ana Lúcia Simões Borges (2018)
The objective of this thesis is to investigate the first effects provoked by the Law 13.415, of February 2017, which concerns the offering of English in the curriculum of Elementary School, as of the sixth grade, and imposes its obligatority in the curriculum of High School, which ends up provoking negative impacts in the Brazilian education system for being contrary to the linguistic and social rights of the school communities, which were enshrined in the LDBEN of 1996 and in the documents arising from it, such as PCN, OCEM, BNCC, etc., revealing the law is inconsistent towards studies and research on the matter. To investigate the ways English, as a school discipline, became part of the obligatory curriculum of the Basic Education, after having its hegemony threatened, in 2005, by the so-called Law of Spanish, and after having been considered part of a complementary component in the school curricula, I analyzed the way it consolidated its hegemony in the school curriculum and its current situation regarding the educational policies related to the teaching of languages, based on the historiography and on the works in the field of the History of Language Teaching (ALMEIDA FILHO, 2005; OLIVEIRA, 2010, 2017; SANTOS, 2017; VIDOTTI, 2010); History of School Disciplines (CHERVEL, 1990; CHERVEL e COMPÈRE, 1999); studies on curriculum (GOODSON, 2005); pioneer works in the field of Applied Linguistics that contributed to a history of the teaching of languages in Brazil (CHAGAS, 1976; CARNEIRO LEÃO, 1935); studies on the role of foreign languages in the formation and internationalization of education and which point to English as the global lingua franca (KACHRU, 1992; PHILLIPSON, 1992; CRYSTAL, 1999; SEIDLHOFER, 2001; JENKINS, 2006, 2009; PENNYCOOK, 2002, 2006, 2010, 2017) and studies on language policies (FISHMAN, 1974; TOLLEFSON, 2002; SPOLSKY, 2004, 2009, 2012; SHOHAMY, 2006; RAJAGOPALAN, 2006; CALVET, 2007), aiming to contribute to the deepening and to the increase of the time scope of the history of the teaching of languages in Brazil. The period chosen for the analysis begins in 1961, the year of the promulgation of the first version of the Law of Basic Guidelines, also including the Law 5.692/71, the Law 9.394/96, the current version of LDBEN, and ends in 2017, with the analysis of the Law 13.415/17. The legislation and the educational historiography were the research sources I made use of in this thesis. With this study, I concluded it is necessary to subsidize actions that lead to the formulation of articulated language policies that deal with the continuity or the practice of the effective teaching of other languages, so that the massive teaching of English makes way to the development of plurilingual curricula.________________________________________________________________________________________________________________________________